Spatial Frames of Reference and Non Digital Way-finding: A Longitudinal Study of Cultural Persistence in Namibian and Inuit Communities - Muhammad Ridwan; Belay Sitotaw Goshu (Lakhomi Journal Scientific Journal of Culture, 2026)
This longitudinal study (2005–2025) examined cultural persistence in spatial frames of reference (FoRs) and non‑digital wayfinding among the ≠Akhoe Haiǁom of Namibia (n = 84) and Inuit of Igloolik, Nunavut (n = 72). Across three waves, absolute (geocentric) FoRs remained predominant in both communities, with no significant population‑level decline Haiǁom: 78 % to 74 %; Inuit: 72 % to 69 % (both p  > 0.05). However, significant generational differences emerged: younger participants (≤ 30 years) showed lower absolute FoR preference than older adults (≥ 50 years) in both groups (Haiǁom: 69 % vs. 82 %; Inuit: 62 % vs. 77 %; β = 0.42 and 0.39, respectively, p < 0.01). Importantly, the generational gap did not widen over time (no wave × cohort interaction). Self‑reported GPS use rose dramatically (Haiǁom: 4 % to 41 %; Inuit: 12 % to 67  %), yet increased GPS use was not associated with diminished wayfinding accuracy when controlling for age (β = 0.07, 95 % CI [–0.03, 0.17], p = 0.16). Qualitative data revealed that participants actively domesticated GPS as a supplemental tool, preserving geocentric strategies for primary orientation. These findings support a model of adaptive persistence, wherein core orienting schemas resist rapid transformation while peripheral strategies undergo selective innovation. We conclude that culturally embedded FoRs constitute a resilient cognitive resource, with implications for theories of cultural cognition, indigenous knowledge preservation, and the design of culturally responsive navigation technologies.